THE ATTITUDES OF FOOTBALLERS BELONGING TO DIFFERENT RANKS OF COMPETITION TOWARDS ALLOWED STIMULATION RECOVERY MEDICINES - Miroslav Smajić; Bogdan Tomić; Alen Kapidžić; Aleksandar Joksimović (Sport Scientific And Practical Aspects, 2025)
Allowed stimulation recovery medicines are the substances and methods having physiological impact on the increase of sportsman’s effect and with the aim of more effective recovery, that is to say, improving sports results that can hard be achieved by training means and methods, and they may be regarded as useful as long as they are used as a complement to training. If they are used wisely, they can increase the resistance of organism of sportspeople to training and competition stress and they have optimal effect on removing general and local fatigue. The aim of research lies in checking and analyzing the attitudes of footballers belonging to different ranks of competition on allowed stimulation recovery medicines. The sample of respondents consists of 120 footballers belonging to different ranks of competition (Super League of Serbia = 43, The Prime League of Serbia = 40, and Serbian League = 37). The sample of variables consists of the system of 10 attitudes (statements), and each attitude (statement) contains 5 verbal categories (marked from -2 to +2). Multivariate analysis of variance (MANOVA) and analysis of variance (ANOVA) are applied for determining multivariate and univariate significance of differences among footballers belonging to different ranks of competition. By analyzing the attitudes of footballers belonging to different ranks of competition to allowed stimulation recovery medicines it can be concluded that footballers are non-divided in the attitudes that allowed stimulation recovery means are applied in a purposeful and optimal way.